What Lies Behind the Students’ Need in English for Specific Purposes: A Reflection of Needs Analysis - Umi Rachmawati (Journal of Languages and Language Teaching, 2020)
This study was a need analysis study as a part of the research and development of instructional materials for English for Business (EFB) at Universitas Muhammadiyah Magelang. This study was aimed at finding the students’ needs on their EFB course in terms of their personal characteristics, English proficiency assumption, learning motivation, and personal interest in their learning English. This study was conducted in a qualitative study that involved the nature of the qualitative study in nature. The findings of the study indicated that (1) the students’ were adolescents that were ready and conscious to get the lesson, (2) the students felt that they did not have good English mastery, (3) the students’ motivation in learning individually was not as high as learning in groups though they realized that they needed to master the target language, and (4) the students’ preferred to have more topics on Islamic values and functions in English and teacher’s roles are planner, information provider, and resource developer.